2013
DOI: 10.4274/mirt.69775
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Somatostatin Receptor Imaging with In-111 Octreotide and/or Ga-68 DOTATATE in Localizing Ectopic ACTH Producing Tumors

Abstract: Objective: We aimed to evaluate the value of somatostatin receptor imaging (SRI) with In-111 octreotide and Ga-68 DOTATATE in localizing ectopic ACTH producing tumors.Methods: Nineteen patients who had In-111 octreotide somatostatin receptor scintigraphy (SRS) and/or Ga-68 DOTATATE PET-CT to localize ectopic ACTH producing tumors between the years 2000 and 2012 were included retrospectively in our study. The results of SRI were compared with clinical onset, radiological findings and surgical data of the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 32 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…There are very few studies comparing PET/CT with PET imaging. In the study of Ozkan et al, one lung neuroendocrine tumor was identified by 68 Ga-DOTATATE PET/ CT which the CT of the thorax could not detect [31]. About the 4 tumors detected by PET as source of ectopic Cushing syndrome in the study by Kakade et al, only two of them were already localized by CT [30].…”
Section: Comparative Analysis Of the Different Tracers And Modalitiesmentioning
confidence: 91%
See 2 more Smart Citations
“…There are very few studies comparing PET/CT with PET imaging. In the study of Ozkan et al, one lung neuroendocrine tumor was identified by 68 Ga-DOTATATE PET/ CT which the CT of the thorax could not detect [31]. About the 4 tumors detected by PET as source of ectopic Cushing syndrome in the study by Kakade et al, only two of them were already localized by CT [30].…”
Section: Comparative Analysis Of the Different Tracers And Modalitiesmentioning
confidence: 91%
“…Ö zkan et al also demonstrated that 68 Ga-DOTATATE PET/CT could be a promising imaging modality for this indication [31].…”
Section: Somatostatin Analogs Labeled With 68 Gamentioning
confidence: 97%
See 1 more Smart Citation
“…Crucially, both techniques depend on tumoral expression of SSTRs (especially SSTR subtypes 2 and 5) and this, coupled with the difficulties inherent in visualising very small lesions, explains why they have found only limited use in CD. Even in EAS there is considerable heterogeneity of SSTR2 and SSTR5 expression with scan sensitivity reported to be of the order of 40-70% (27). 18 F-FDG uptake is linked to tumour glucose metabolism, as opposed to receptor binding, and hence lesions that do not express SSTRs, and are not visualized with octreotide scans, may theoretically be detected with 18 F-FDG-PET (PET/CT) (28).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…The two modalities most commonly used in clinical practice are 111 In-pentetreotide scintigraphy ('octreoscan') and 68 Ga-DOTATATE or 68 Ga-DOTATOC PET/CT. Although both can theoretically be employed to detect ACTH-secreting tumours at any site, it is predominantly in EAS that their role has been established (27). While conventional SSTR scintigraphy lacks spatial resolution (especially for lesions !2 cm), this can be partly overcome through the use of SPECT (singlephoton emission computerised tomography) for image acquisition.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%